Chirality communications between inorganic and organic compounds. (16th February 2021) - Ni, Bing; Cölfen, Helmut
Abstract : Chirality communications between inorganic and organic compounds bridge the gap between different materials. The transfer is mainly realized by material hybridization andasymmetric synthesis, while the recognition is usually carried out in the form of enantioselective adsorption of organics on inorganics. The transfer and recognition can enlarge the number of chiral materials, which may lead to new applications in many fields.